Molecular phylogeny and morphology reveal a new species of Exidia (Auriculariaceae, Auriculariales) from Yunnan Province, China - Jiang, Yingtao; Wang, Lu; Zhou, Chunqin; Shen, Kaize; Zhang, Sicheng; Yang, Ali; Zhao, Changlin (Phytotaxa, 2025)
In this study, Exidia punctata is described and illustrated as a novel species based on morphological characteristics and phylogenetic analyses of internal transcribed spacer (ITS) regions and the large subunit (nLSU) of nuclear ribosomal RNA genes. The species is characterized by smooth, membranaceous, cushion-shaped basidiomata with white to cream hymenial surface, and narrowly cylindrical to allantoid basidiospores (13–15.5 × 5–6.5 µm). The phylogenetic tree inferred from ITS+nLSU sequences revealed that the new species was nested into the genus Exidia within the family Auriculariaceae, in which it grouped with the clade comprising E. glandulosa, E. pithya, E. reflexa and E. subglandulosa.